Evaluation Of CCTV Operator Work Performance Reviewed from the Aspects of Ergonomics: Working Methods, Posture, And Environmental Conditions - Clea Putri, Famelga; Erniyani, Erniyani (PT. SAFARI AMALIA, 2025)
CCTV monitoring activities are static tasks that require continuous visual focus and prolonged sitting, making operators prone to physical fatigue, visual impairment, and decreased performance. Common problems include non-ergonomic work postures, thermal discomfort, and lighting glare on monitors. This study aims to evaluate CCTV operator performance through a comprehensive ergonomic approach that includes posture analysis, work activity patterns, and environmental conditions. The methods used include work sampling to measure the proportion of productive and idle time, posture analysis using REBA to determine musculoskeletal risk, and measurement of environmental parameters such as temperature, air velocity, viewing distance, and lighting quality. The results showed a REBA score of 3 (low risk but improvement needed), operator focus time of only 8–10 minutes, normal idle time of 15 minutes, and an allowance of 17 minutes. Nighttime thermal conditions were below comfort standards, and glare was found to interfere with visibility. These findings confirm the need to redesign workstations and improve working conditions to improve CCTV operator performance.